The role of personal loans in the financing of SMEs - Briozzo, Anahi Eugenia (2014)
This work studies the determinants of the use of personal loans in small and medium-sized enterprises (SMEs). Design/methodology/approach: Personal loans are addressed as a function of the borrower and collateral. To empirically test the hypothesis of this study, a probit model was applied to a group of companies in Bahia Blanca, Argentina, with a previous analysis of the possible effects of sample selection. Findings: Older companies, firms with lower expected growth rates, younger owners who seek to create value or growth, and those who perceive low emotional costs associated with bankruptcy, are less likely to use personal loans to finance their operations. Research limitations/implications: This study is limited by the availability of data on SMEs in Argentina. Social implications: The results highlight the importance of financial aid programs that focus on SME scarce availability of collateral. Originality/value: This study makes three principal contributions: i) it investigates the phenomenon of personal loan utilisation in SMEs; ii) it analyses financing decisions from both the supply and demand perspectives; and iii) it presents a database that includes variables that have not been previously studied in Argentina or other emerging economies.